Asymmetric induction on isocyanide-based transformations: development of stereoselective Ugi-type reactions - Silva, Vitor Alcantara Fernandes da (Universidade Federal de São Carlos, 2023)
The design of new synthetic transformations that rapidly allow construction of structurally complex molecules from simple starting materials under both concepts of diversity and function-oriented syntheses is extremely desirable in contemporary organic chemistry. In this regard, multicomponent reactions (MCRs) appear as one of the most useful strategies for quickly generating structural diversity and molecular complexity. Among the vast repertoire of MCRs, isocyanide-based multicomponent reactions (IMCRs) stand out as a powerful approach to achieve highly functionalized molecules with elevated chemical efficiency, convergence and atom economy. As part of our ongoing interest in developing diastereoselective intramolecular I-MCRs based on chiral scaffolds, an efficient strategy has been established, which combines the stereocontrol of organocatalysis with the diversity-generating character of multicomponent reactions, leading to structurally unique cyclopentenyl frameworks containing two stereogenic centers. Based on our recent success into using hemiacetals in substrate-controlled I-MCR reactions, we have envisioned the development of an asymmetric Ugi-type Reaction with achiral hemiacetals using an organocatalytic Brønsted acid as the element of asymmetric induction. After a short screening of conditions, we found out that SPINOL-derived chiral phosphoric acids, especially with phenanthryl as substituent (59% yield, 66% ee), which was chosen as the best catalyst in this initial screening.
Indução assimétrica em transformações baseadas em isocianetos: desenvolvimento de reações estereosseletivas tipo Ugi
Keywords: Organocatálise; Reação Multicomponente; Reação de Ugi; Hemiacetal; Organocatalysis; Ugi reaction; Isocyanide; Isocianeto; Multicomponent reaction; Transformações estereosseletivas; Stereoselective transformations; Asymmetric induction; Indução de assimetria; Chiral Phosphoric Acid; Ácido fosfórico quiral; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA